Characterization of antibiotic susceptibility and high level aminoglycoside resistant genes in Enterococcus faecalis and Enterococcus faecium clinical isolates - Moussa, Ayan Aden (2018)
Enterococcus faecium and Enterococcus faecalis are among the predominant species causing hospital-acquired infections, with high mortality and morbidity rates. Enterococci which exhibit high level aminoglycoside (HLAR) and vancomycin resistance (VRE) possess a significant problem in therapeutic treatment. These resistance strains are becoming more widespread in Europe, USA and Asia. Studies have shown that the different distributions of aminoglycoside modifying enzymes (AMEs) among HLAR are based on the geographical regions. In Malaysia, however, data on the prevalence of HLAR and the distribution of AMEs are still limited. Hence, the aims of this study were to determine the antibiotic susceptibility patterns of the clinical isolates E. faecalis and E. faecium and the distribution of HLAR genes among the resistant isolates. Seventy-five clinical enterococci isolates used in this study were originally obtained from a tertiary centre, in the year 2009 and 2010. These isolates were isolated from different sources including pus (50%), blood (32%), urine (11%) and other sources such as CSF and HVS (7%). Reidentification of these isolates was carried out using several methods including sub-culturing on selective medium and Gram staining, followed by confirmatory tests using a commercial biochemical profiling (API20 strep) and 16s rRNA PCR amplification. Antimicrobial susceptibility tests were performed using disc diffusion, E-test and broth microdilution methods. The antibiotics used were aminoglycosides (gentamicin, streptomycin, kanamycin, amikacin, tobramycin) and other antibiotics which are commonly used in the hospital to treat enterococcal infections such as ampicillin, vancomycin, erythromycin, tetracycline, chloramphenicol and linezolid. Detection of HLAR genes was performed on resistance isolates using single PCR amplifications. Out of 25 (33.3%) isolates of E. faecium, 84% and 68% showed high level gentamicin resistance (HLGR) and high level streptomycin resistance (HLSR), respectively. Resistance against erythromycin and tetracycline were 100%, while ampicillin and chloramphenicol showed 84% and 32% resistance rates, respectively. None of the E. faecium isolates showed resistance towards vancomycin and linezolid. On the other hand, all 50 (66.7%) E. faecalis isolates were resistance to all aminoglycosides tested with the following percentages; amikacin (100%), kanamycin (90%), tobramycin (70%), HLGR (36%) and HLSR (46%). These isolates were also resistance to tetracycline (98%), erythromycin (96%), chloramphenicol (46%), ampicillin (24%), linezolid (8%), and vancomycin (4%). Interestingly, the E. faecalis isolates that were resistant to vancomycin were previously reported as susceptible. In this study, E. faecium exhibited higher resistance rates to all antibiotics except vancomycin and linezolid compared to E. faecalis. Additionally, 46% of E. faecalis showed MIC of streptomycin up to 1042 μg/mL while another 36% showed MIC of gentamicin equal to 512 μg/mL. The MIC of aminoglycosides determined in this study showed similar level as observed in other countries, despite the variation of the methods used. The presence of aminoglycoside modifying enzyme (AME) genes [aac(6)-Ie-aph(2)- Ia, aph(2)-Ib, aph(2)-Ic, aph(2)-Id, aph(3)-IIIa] were detected using PCR amplification. The results demonstrated that the HLGR gene, aac(6)-Ie-aph(2)- Ia and the HLSR gene, aph(3)-IIIa were detected in 32% and 40% of E. faecalis and E. faecium resistance isolates, respectively. The spread of these genes were responsible for high level resistance to gentamicin and streptomycin among enterococci isolated in this study. As HLAR genes are highly transferable to not only among the enterococci species but also among various bacterial species, continuous antibiotic surveillance in Malaysian hospitals is warranted in future and preventive measures can be implemented accordingly.